Phytochemical Profile and Antidiabetic, Antioxidant, and Anti-Inflammatory Activities of Gypsophila paniculata Ethanol Extract in Rat Streptozotocin-Induced Diabetes Mellitus - Lia-Oxana Usatiuc; Marcel Pârvu; Raluca Maria Pop; Ana Uifălean; Dan Vălean; Csilla-Eniko Szabo; Mădălina Țicolea; Florinela Adriana Cătoi; Floricuța Ranga; Alina Elena Pârvu (MDPI AG, 2024)
The present study aimed to investigate the effects of the Gypsophila paniculata ethanol extract (GPEE) on oxidative stress, inflammation, and metabolic markers in a rat model of streptozotocin-induced diabetes mellitus (DM). Phytochemical analysis using high-performance liquid chromatography coupled with mass spectrometry was performed to measure the total phenolic and flavonoid contents. In vitro antioxidant activity was evaluated through DPPH, FRAP, H2O2, and NO scavenging tests, and the in vivo effects of the GPEE were assessed in streptozotocin-induced DM rats. Treatments with the GPEE, metformin, and Trolox were administrated by gavage for 10 days. On day 11, blood was collected, and serum oxidative stress (total oxidative status, oxidative stress index, malondialdehyde, advanced oxidation protein products, 8-hydroxydeoxyguanosine, nitric oxide, 3-nitrotyrosine, advanced glycation end-products, total antioxidant reactivity, total thiols), inflammatory (IL-1β, NF-κB, IL-18, and gasdermin D), metabolic (fasting glucose, total cholesterol, triglycerides, and triglyceride-glucose index), and liver injury (AST, ALT, and AST:ALT ratio) markers were measured. The GPEE was found to have a significant polyphenols content and a moderate in vitro antioxidant effect. In vivo, the GPEE lowered oxidants and increased antioxidants, decreased inflammatory markers and blood glucose, and improved lipid profiles and transaminases in a dose-dependent manner, with higher doses having a better effect, being comparable to those of metformin and Trolox.